Foliage Water Loss Pattern in Sal (Shorea robusta Gaertn.f.) and Its Associates under Stress - Chauhan, P. S.; Kumar, Rakesh; Negi, J. D. S. (Indian Forester, 2002)
An attempt has been made to understand the foliage water loss pattern in Sal forest in Barkot Forest Range of Dehra Dun Forest Division. The study reveals that heavy canopy opening resulted in increase in atmospheric temperature, which is causing stressful environment for the community. Under this stressful environment Mallotus philippensis appears to be drought tolerant species, which can cope with the adverse environment conditions to some extent. This has the conformity that in the Sal forest, where the moisture has become the limiting factor, Mallotus philippensis is the only species, which is colonising during the phase of retrogressive succession.